Surrealist sorcery: objects, theories, and practices of magic in the surrealist movement - Atkin, Will (Transnational surrealism, 2025)
"Often regarded as an artistic movement of interwar Paris, Surrealism comprised an international community of artists, writers, and intellectuals who have aspired to change the conditions of life itself over the course of the past century. Consisting of a wide range of dedicated case studies from the 1920s to the 1970s, this book highlights the international dimensions of the Surrealist Movement, and the radical chains of thought that linked its followers across the globe: from France to Romania, and from Canada to the former Czechoslovakia. From very early on, the surrealists approached magic as a means of bypassing, discrediting, and combatting rationalism, capitalism, and other institutionalized systems and values that they saw to be constraining influences upon modern life. Surrealist Sorcery maps out how this interest in magic developed into a major area of surrealist research that led not only to theoretical but also practical explorations of the subject. Taking an international perspective, Atkin surveys this important quality of the movement and how it's remained an important element in the surrealist project and its ongoing legacy"--